Selective PF4 Release In Vitro Induced by Heparin and Related Glycosaminoglycans (GAGs) - Correlation with β-TG Release and Platelet Aggregation - Cofrancesco, E; Colombi, M; Cristoforetti, G; Pogliani, E M (Thrombosis and Haemostasis, 1984)
We studied human platelet aggregation and β-TG/PF4 release induced by heparin and related GAGs in vitro both in normal PRP and in PRP after aspirin. In our experimental conditions, heparin and related GAGs always caused PF4 release in vitro from normal platelets, whether or not there was measurable platelet aggregation in the aggregometer. Significant β-TG release was induced only by the mucosal heparin preparation (which also induced platelet aggregation in some citrated PRP). Therefore, while β-TG release in vitro seems to correlate with platelet aggregating activity of heparin, the selective PF4 release, caused by heparin and related GAGs also in conditions in which neither platelet aggregation nor β-TG are measurable, is probably associated with the high affinity of PF4 for heparin. The degree of affinity of GAGs for PF4 (heparin > DeS > HS) seems to correlate with PF4 release. Moreover, the significant reduction in PF4 release in vitro after aspirin suggests that GAGs-induced PF4 release is related to a cyclooxygenase-dependent activation process.
Keywords: Heparin; Glycosaminoglycans; Platelet aggregation; Beta-thromboglobulin; Platelet factor 4; Platelet release